Acute myeloid leukemia & related neoplasms : selected chapters from hematology - Farkaš, Firas (Comenius University in Bratislava, 2021)
This scriptum is written for students of general and dental medicine in the under- graduate and doctoral degrees and was created as a supplementary teaching text to the subject of hematology. It focuses mainly on practical aspects and innovative approaches. The main part of the innovation was the creation of actual teaching materials and their enrichment with illustrations. Its aim is to acquaint the reader with the basics of selected chapters in the field of hematology. This textbook deals with acute myeloid neoplasms and their complications, including CNS and extramedullary leukemia. It describes their diagnostics and management in detail. ----------Toto skriptum je napísané pre študentov všeobecného a zubného lekárstva v pregraduálnom a doktorandskom stupni štúdia a vzniklo ako doplnkový učebný text k predmetu hematológia. Zameriava sa najmä na praktické aspekty a inovatívne prístupy. Hlavnou časťou inovácie bolo vytvorenie aktuálnych učebných materiálov a ich obohatenie o ilustrácie. Jeho cieľom je oboznámiť čitateľa so základmi vybraných kapitol z oblasti hematológie. Táto učebnica sa zaoberá akútnymi myeloidnými novotvarmi a ich komplikáciami, vrátane CNS a extramedulárnej leukémie. Podrobne popisuje ich diagnostiku a riadenie.